If it's not what You are looking for type in the equation solver your own equation and let us solve it.
v in (-oo:+oo)
2/7+2/7 = (-4/5)*v-((3/5)*v) // - (-4/5)*v-((3/5)*v)
(3/5)*v-((-4/5)*v)+2/7+2/7 = 0
(4/5)*v+(3/5)*v+2/7+2/7 = 0
7/5*v+4/7 = 0 // - 4/7
7/5*v = -4/7 // : 7/5
v = -4/7/7/5
v = -20/49
v = -20/49
| sx-5=9 | | 2(2x+4)=3x+12 | | 18x^2-132x+242=0 | | 8(x+1)-11=53 | | x+0.068x= | | x+x+5+2(x+5)=431 | | 3x+-14=x | | a^2-15a-40=0 | | 33-4x=2x-3 | | 6y=4-12 | | 3a/4-7/4=4a/3+5/3 | | 3x+10=17+2x | | x+0.068= | | m^2+7m-12= | | 7/3=2w | | 4(x+1)-11=53 | | 5(x+1)-11=53 | | -6(x+1)-11=53 | | 60=-16x^2+85x | | x+2/3-1/2=x/3-2(x-2)/3 | | -3x-3(-5x-17)=17 | | -4h+16=22+2 | | 12+2(3p-4)=22 | | 11-6m-20=20-5m | | 5x+3=6x-14 | | 3b+2(b-3)=91.50 | | 8x-(-2+3)=11 | | 1/4(x-4)+x=14 | | 6x-12-3=x+27-9x | | 5/10+7/3 | | (2x-3)(x^3-x^2+3x+5)=0 | | 2x-2x+3=8 |